Visions of Germany and Austria [videorecording (DVD)] (Visions travel series, 2016)
Experience the fairy tale beauty, natural wonders, and rich history of southern Germany. Then, journey to Austria, and see the essence of what was called Central Europe's crown jewel. Shot in high definition from a helicopter-mounted camera, each tour invites you to linger, for the total experience of a virtual vacation.